IMPLEMENTATION OF MULTI-NODE SENSOR DATA DELIVERY USING THE MASTER-SLAVE METHOD IN LORA COMMUNICATION - Hendry, Hendry; Manongga, Daniel (Journal of Technology Informatics and Engineering, 2024)
This research explains the application of sending data from various sensor nodes using the master-slave method in Long Range (LoRa) communication. This system was created to increase efficiency and reliability in collecting sensor data spread across several locations. Sensor nodes function as slaves that collect and send data to the master. The master then processes and combines the data before sending it to a central server. Experimental results show that this method is successful in reducing latency and increasing data transmission speed and shows great potential for Internet of Things (IoT) applications that require wide communication range and low power consumption.